1993
DOI: 10.1093/carcin/14.7.1303
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage resulting from the oxidation of hydroquinone by copper: role for a Cu(II)/Cu(I) redox cycle and reactive oxygen generation

Abstract: The myelotoxicity, including leukemia, associated with benzene exposure has been attributed to the further activation of benzene-derived metabolites. In a previous study, we observed that (Cu(II) strongly mediates the oxidation of hydroquinone (HQ) producing benzoquinone (BQ) and H2O2 through Cu(II)/Cu(I) redox mechanism. Since copper exists in the nucleus and is closely associated with chromosomes and DNA, in this study we investigated whether this chemical--metal redox system induces strand breaks in phi X-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(137 citation statements)
references
References 0 publications
5
130
0
2
Order By: Relevance
“…42 The presence of singlet oxygen scavengers but not hydroxyl radical scavengers provided partial protection, suggesting that singlet oxygen rather than hydroxyl radical may play a role in the induction of DNA strand breaks. However, these scavengers are lacking in absolute specificity, 7 and the involvement of singlet oxygen may be small because there is currently no known mechanism by which it can be formed from oxyradicals, although Steinbeck et al 43 have reported that phagocytosing neutrophils can generate singlet oxygen intracellularly.…”
Section: Coppermentioning
confidence: 96%
“…42 The presence of singlet oxygen scavengers but not hydroxyl radical scavengers provided partial protection, suggesting that singlet oxygen rather than hydroxyl radical may play a role in the induction of DNA strand breaks. However, these scavengers are lacking in absolute specificity, 7 and the involvement of singlet oxygen may be small because there is currently no known mechanism by which it can be formed from oxyradicals, although Steinbeck et al 43 have reported that phagocytosing neutrophils can generate singlet oxygen intracellularly.…”
Section: Coppermentioning
confidence: 96%
“…The method is as described by Li and Trush (1993) with some modifications. Briefly, 0.1μg of DNA was incubated with various chemicals in KPB, pH 7.4 at 37 o C for 30 min (final volume 10 μl).…”
Section: Induction Of Strand Breaks In Plasmid Dnamentioning
confidence: 99%
“…80 µg of copper, with the total 130 blood concentration of copper about 16 µM. 41 Copper can become available in vivo for Fenton reactions to occur, as it is present in blood plasma as metalloproteins and as a number of transport and storage complexes. Copper also exists, however, in the cell nucleus where it may be involved in the 135 condensation of DNA-histone fibres into higher order chromatin structures.…”
Section: Introductionmentioning
confidence: 99%